Physical activity for muscle rehabilitation in sarcopenia - N. B. R. Alves, Fernanda; S. Pedro, Wilson José; R. Afonso, João Pedro; A. Souza, Shayra Kellen; O. Moura, Barbara; P. M. Neto, Joaquim; S. I. Tabata, Keyci; R. Alves, Larissa; V. Braga, Lenita; Ribeiro, Marcos André; V. Barbosa Júnior, Flávi; Hanna, Helias; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: sarcopenia is a progressive and generalized clinical condition associated with loss of mass, strength, and/or muscle function, impairing physical performance. The definition of sarco-penia is a dilemma, as several studies have been published in the last ten years by different socie-ties. One of the most used definitions is the Guideline created by the European Working Group on Sarcopenia in Older People (EWGSOP) and updated in 2019 (EWGSOP2) to facilitate the under-standing of sarcopenia and improve treatment proposals. This is the only definition supported by several international scientific societies for clinical practice and research in patients with sarcope-nia. Treatment can be divided into non-pharmacological and pharmacological. There are no spe-cific drugs approved for the treatment of sarcopenia. As for non-pharmacological interventions, physical exercise is the most effective intervention, especially resistance exercises. Nutritional in-tervention has a low level of evidence. Objectives: The objective of this article is to review data on the effect of physical exercise in the treatment of sarcopenia. Method: Reviews and systematic re-views were searched in different data sources, including PubMed, between the years 2010 and 2024, with the keywords (sarcopenia and non-pharmacological treatment; sarcopenia and exercise and sarcopenia). Conclusions: Physical exercise is the first-line treatment for sarcopenia. There is no drug released for the specific treatment of sarcopenia, and nutritional interventions have little clinical evidence in improving the quantitative and functional aspects of the muscular system in sarcopenic patients. Among the exercise modalities, resistive exercises alone showed the most sig-nificant benefit in the muscular rehabilitation of sarcopenic patients. Despite this, when evaluated with resistive exercise, aerobic and balance exercises brought additional benefits in some muscular functions. Nutritional intervention also appears to improve muscle strength when associated with resistive exercises. More studies are needed to elucidate the best physical activity program and whether other nutritional interventions could benefit the patient more.